Linking the school children of the mixed center "mártires de Bolivia" to the knowledge of beekeeping in Cuba - Armiñana-García, Rafael (2024)
Beekeeping is a competitive, equitable and sustainable system because of its low resource consumption and environmental impact, and because it contributes to technological development, since it creates jobs, produces food and helps improve the quality of life of workers. The purpose of the study is to propose a system of activities to disseminate knowledge about beekeeping in Cuba to 8th grade “B” students of the mixed center “Martínez de Bolivia”, located in the town of Buena Vista, in the municipality of Remedios, Villa Clara, Cuba. In carrying out the research work, information collection and processing methods were used, such as: collective observation, documentary analysis, survey, interview, expert criteria, historical-logical, modeling and others. The application of the information collection methods to the 25 schoolchildren who made up the sample made it possible to reveal the insufficient knowledge possessed by the schoolchildren on the subject under study. The experts evaluated the proposal as very relevant. Its validation contributed to the acquisition of new knowledge on beekeeping in Cuba and its importance.